(untitled) (CIPEEX, 2025)
The quest for a perfect smile that is pleasing to the eye has made cosmetic treatments highly relevant, increasing the demand for procedures that meet these needs. Direct composite resin restorations are widely used for aesthetic solutions in various clinical situations. Objective: To report the clinical case of a patient with worn incisal edges of the anterior upper teeth, which led to loss of aesthetics. Using a minimally invasive restorative approach, the incisal edges were augmented with direct composite resin restorations to restore aesthetics. Case report: The patient, IBC, female, attended the UniEVANGÉLICA Dental Clinic complaining of aesthetic dissatisfaction, with the main complaint being “sensitivity in the upper front teeth, because they were worn and also ugly, because they were small.” Upon performing an intraoral examination, wear was noticed on the incisal edges of the anterior upper teeth. The proposed treatment plan was to perform restorations with composite resin using the direct technique to reconstruct the incisal edges, following the clinical restoration protocol. The final finishing and polishing were left for the subsequent session. Conclusions: Adhesive restorative procedures showed excellent aesthetic and functional results, exceeding expectations. Composite resins are increasingly versatile, meeting various clinical demands and enabling aesthetic restorative procedures that correspond to patients’ aesthetic appeals, with an excellent cost-benefit ratio.